Microenvironmental considerations in the application of human mesenchymal stem cells in regenerative therapies - Steven J Greco (Dove Medical Press, 2008)
Steven J Greco1, Pranela Rameshwar21Graduate School of Biomedical Sciences; 2Department of Medicine, Division of Hematology/Oncology, University of Medicine and Dentistry of New Jersey-New Jersey Medical School, Newark, NJ, USAAbstract: The therapeutic utilization of stem cells has been ongoing for several decades, principally in the form of bone marrow (BM) transplants to treat various hematological disorders and other immune-related diseases. More recently, stem cells have been examined as a potential therapy for a multitude of other diseases and disorders, many of which are currently untreatable. One consideration that poses a formidable task for the successful clinical application of stem cells in new disease models is the impact of the host tissue microenvironment on the desired therapeutic outcome. In vitro, stem cells exist in surroundings directly controllable by the researcher to produce the desired cellular behavior. In vivo, the transplanted cells are exposed to a dynamic host microenvironment laden with soluble mediators and immunoreactive cells. In this review, we focus on the possible contribution by microenvironmental factors, and how these influences can be overcome in therapies utilizing mesenchymal stem cells (MSCs), such as for graft versus host disease, multiple sclerosis and ischemia among others. Specifically, we examine three ubiquitous microenvironmental factors, IL-1α/β, TNFα, and SDF-1α, and consider how inhibitors and receptor antagonists to these molecules could be applied to increase the efficacy of MSC therapies while minimizing unforeseen harm to the patient.Keywords: cytokine, microenvironment, mesenchymal stem cells, bone marrow